Legal Implications of Law Number 17 of 2023 on Health for SOPs and Risk Management in Hospitals - Rahma, Alfiyyah; Prayuti, Yuyut (Research Horizon, 2025)
The promulgation of this law marks a paradigm shift in Indonesia’s health law system, emphasizing accountability, transparency, and patient safety as the core principles of healthcare service delivery. This study aims to analyze the legal implications of the enactment of Law Number 17 of 2023 on Health for the formulation of standard operating procedures and the implementation of risk management in hospitals. The method used in this research is library research with a normative juridical approach. The findings indicate that the changes in legal norms under Law Number 17 of 2023 have led to the necessity of adjusting hospital SOPs to be oriented toward risk analysis and patient safety. The implementation of risk management is now viewed as a legal obligation inherent in healthcare institutions rather than merely a managerial instrument. This research also reveals an urgent need for hospitals to establish legal risk management units to anticipate potential legal disputes and strengthen legal protection for medical personnel. The conclusion of this study emphasizes that the enforcement of the new Health Law brings positive implications in strengthening a legally grounded, professional, and equitable hospital governance system.